PAW25 A single-centre, pilot, randomised controlled trial of recombinant human erythropoietin in primary progressive multiple sclerosis. Issue 11 (22nd October 2010) - Karpha, I; Ramtahal, J; Boggild, M; Evans, F
Abstract : Introduction: There is currently no disease modifying therapy for PPMS, which constitutes 10–15% of MS cases. rhEPO is has previously been suggested to have a neuroprotective role in an open label, exploratory study of rhEPO in progressive MS. Methods: A pilot randomised controlled trial of rhEPO vs placebo was performed in 21 subjects with PPMS at The Walton Centre, Liverpool. rhEPO (30 000 IU IV) was given weekly for 12 weeks, with follow-up at week 13, 17 and 21. Primary outcome measures were maximum walking distance (MWD) and Expanded Disability Status Scale (EDSS). Results: There was a nonsignificant improvement in MWD in the rhEPO arm (p=0.879) although there was no change in EDSS. The rhEPO arm performed significantly worse on MSFC (p=0.042). There was a higher frequency of adverse events in the rhEPO arm, although there were no serious adverse events. Consequently, only two of 11 patients completed the 12 week rhEPO regimen. One patient required venesection due to polycythaemia, and the rhEPO arm showed a significantly higher red cell count, haemoglobin and packed cell volume posttreatment than placebo (p=0.004, 0.004 and 0.024 respectively). Conclusion: Despite the large proportion of dose omissions, a nonsignificant improvement in MWD was found, particularly in those receiving the majority of the active treatment. Future trials should address the safety issues highlighted here; alterations in the dosage and treatment regimen may improve the drug's safety profile.